2014
DOI: 10.1115/1.4027541
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Draft Tube Surge and Erosive Blade Cavitation in a Full-Scale Francis Turbine

Abstract: A full-scale Francis turbine has been experimentally investigated over its full range of operation to detect draft tube swirling flows and cavitation. The unit is of interest due to the presence of severe pressure fluctuations at part load and of advanced blade suction-side cavitation erosion. Moreover, the turbine has a particular combination of guide vanes (20) to runner blades (15) that makes it prone to significant rotor-stator interaction (RSI). For that, a complete measurement system of dynamic pressures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 4 publications
0
23
0
1
Order By: Relevance
“…[11][12][13]; however, no study has been reported on the investigation of synchronous-and asynchronous-type pressure pulsations in prototypes. Measurements on the model turbines are not completely representative of the prototype and its dynamic behavior [11,[14][15][16][17]. An isolated test facility available in the laboratory has different dynamic characteristics [5,18] and has limited scope for scaling the data.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13]; however, no study has been reported on the investigation of synchronous-and asynchronous-type pressure pulsations in prototypes. Measurements on the model turbines are not completely representative of the prototype and its dynamic behavior [11,[14][15][16][17]. An isolated test facility available in the laboratory has different dynamic characteristics [5,18] and has limited scope for scaling the data.…”
Section: Introductionmentioning
confidence: 99%
“…Č erneticˇ8 and Č udina and Prezelj 14,28 measure the structural vibration signals in audible spectra of kinetic pumps to research the cavitation process and discrete frequency is found. The vibrations and AEs have been combined by Escaler et al 29 to experimentally investigate the draft tube swirling flows and cavitation over the full range of operation in a full-scale Francis turbine. The correlation between the transient cavitating flow structures and the vibration characteristics is analyzed for a modified NACA66 hydrofoil in Wang et al's 30 research.…”
Section: Introductionmentioning
confidence: 99%
“…The methods used to predict cavitation are based on induced high frequency vibrations and acoustic emissions measured on the turbine guide bearing and the guide vanes [2]. A preliminary investigation [3] has already demonstrated the feasibility of the installed measuring system and the applied signal processing techniques to monitor the activity of runner blade cavitation for unit operation above the best efficiency point (BEP). The results are consistent with the hypothesis that the highest risk of erosion would occur at full load.…”
Section: Introductionmentioning
confidence: 99%